Role of Baicalin and Liver X Receptor Alpha in the Formation of Cholesterol Gallstones in Mice. (21st April 2020) - Chen, Geng; Wu, Shuodong
Abstract : This study was aimed at investigating the effect of baicalin on experimental cholesterol gallstones in mice. The mouse gallstone model was induced by feeding with a lithogenic diet, and cholesterol stones were found in the gallbladder. The lithogenic diet caused elevation of triglycerides, cholesterol, and low-density lipoprotein concentrations and descent of high-density lipoprotein concentration in serum. Hyperplasia and inflammatory infiltration were observed in the gallbladder wall of lithogenic diet-fed mice. We also found the increase of cholesterol content and the decrease of bile acid in bile. Real-time PCR and western blot results demonstrated that the expression levels of two enzymes (cholesterol 7 α -hydroxylase (CYP7a1) and sterol 12 α -hydroxylase (CYP8b1)) to catalyze the synthesis of bile acid from cholesterol were decreased and that two cholesterol transporters (ATP-binding cassette transporter G5/G8 (ABCG5/8)) were increased in the liver of lithogenic diet-fed mice. The lithogenic diet also led to enhanced activity of alanine aminotransferase and aspartate aminotransferase in serum; increased concentrations of tumor necrosis factor- α, interleukin- (IL-) 1 β, IL-6, and malondialdehyde; and decreased superoxide dismutase activity in the liver, suggesting inflammatory and oxidative stress. In addition, liver X receptor alpha (LXR α ) was increased in the liver. After gavage of baicalin, the lithogenic diet-induced gallstones, hyperlipidemia, gallbladder hyperplasia, inflammation, and oxidative stress in liver and cholesterol metabolism disorders were all alleviated to some degree. The expression of LXR α in the liver was inhibited by baicalin. In addition, the LXR α agonist T0901317 aggravated lithogenic diet-induced harmful symptoms in mice, including the increase of gallstone formation, hyperlipidemia, hepatic injury, inflammation, and oxidative stress. In conclusion, we demonstrated that baicalin played a protective role in a lithogenic diet-induced gallstone mouse model, which may be mediated by inhibition of LXR α activity. These findings may provide novel insights for prevention and therapy of gallstones in the clinic.